EXPLORING INDONESIAN EFL PRE-SERVICE TEACHERS' PROFESSIONAL IDENTITY - Andana, Yosi; Fithriani, Rahmah (Journal of English Educational Study (JEES), 2024)
Professional identity refers to the self-perception that is related to work. Personal professional identity influences behavior and actions in the work environment. A strong impression of professional identity causes individuals to act in accordance with the norms, ethics, and standards of their profession. Professional identity is an inseparable concept in all professions including the teaching profession. Although much research has examined teachers' professional identity, research on prospective teachers who are still in training is still limited. Many researches emphasis identity among qualified teachers with the assumption that they have a more established identity compared to pre-service teachers who are still developing their professional identities. Acknowledging its importance may encourage further research and contribute to a broader understanding of teacher development, which is informed by knowledge of what factors influence professional identity at all levels. Qualitative descriptive approach is employed in this study. The study is conducted on 13 pre-service teachers majoring in English education who have had field teaching experience. The research instruments used are questionnaires, in-depth interviews, and literature research. Then the data is analyzed using thematic analysis. The findings indicate a crucial factor in the establishing of pre-service teachers' professional self-concept, namely the initial motivation when choosing an English education major. Pre-service teachers also expressed an awareness of the role of professional identity in enabling effective professional performance. Additionally, holding positive perspectives about their chosen profession appears to support skills development that provides new perspectives to the preparation of expert teachers